Bread and Circuses Theories of Mass Culture as Social Decay - Brantlinger, Patrick (Cornell University Press, 1983)
Lively and well written, Bread and Circuses analyzes theories that have treated mass culture as either a symptom or a cause of social decadence. Discussing many of the most influential and representative theories of mass culture, it ranges widely from Greek and Roman origins, through Marx, Nietzsche, Freud, Ortega y Gasset, T. S. Eliot, and the theorists of the Frankfurt Institute, down to Marshall McLuhan and Daniel Bell. Brantlinger considers the many versions of negative classicism and shows how the belief in the historical inevitability of social decay.